Cost‐effectiveness of personal tailored risk information and taster sessions to increase the uptake of the NHS stop smoking services: the Start2quit randomized controlled trial. (11th December 2017) - Wu, Qi; Gilbert, Hazel; Nazareth, Irwin; Sutton, Stephen; Morris, Richard; Petersen, Irene; Galton, Simon; Parrott, Steve
Abstract: Aims: To assess the cost‐effectiveness of a two‐component intervention designed to increase attendance at the NHS Stop Smoking Services (SSSs) in England. Design: Cost‐effectiveness analysis alongside a randomized controlled trial (Start2quit). Setting: NHS SSS and general practices in England. Participants: The study comprised 4384 smokers aged 16 years or more identified from medical records in 99 participating practices, who were motivated to quit and had not attended the SSS in the previous 12 months. Intervention and comparator: Intervention was a personalized and tailored letter sent from the general practitioner (GP) and a personal invitation and appointment to attend a taster session providing information about SSS. Control was a standard generic letter from the GP advertising SSS and asking smokers to contact the service to make an appointment. Measurements: Costs measured from an NHS/personal social services perspective, estimated health gains in quality‐adjusted life‐years (QALYs) measured with EQ‐5D and incremental cost per QALY gained during both 6 months and a life‐time horizon. Findings: During the trial period, the adjusted mean difference in costs was £92 [95% confidence interval (CI) = –£32 to –£216) and the adjusted mean difference in QALY gains was 0.002 (95% CI = –0.001 to 0.004). This generates an incremental cost per QALY gained of £59 401. The probability that the tailored letter and taster session is more cost‐effective than the generic letter at 6 months is never above 50%. In contrast, the discounted life‐time health‐care cost was lower in the intervention group, while the life‐time QALY gains were significantly higher. The probability that the intervention is more cost‐effective is more than 83% using a £20 000–30 000 per QALY‐gained decision‐making threshold. Conclusions: An intervention designed to increase attendance at the NHS Stop Smoking Services (tailored letter and taster session in the services) appears less likely to be cost‐effective than a generic letter in the short term, but is likely to become more cost‐effective than the generic letter during the long term.